FASHION AS A FORM OF SELF-IDENTITY: A SEMIOTIC ANALYSIS OF MILLENNIALS' DRESS STYLE - Elva Gustiaeni Nengsi; Andi Azhar (Suluh Adiluhung Publisher (SAPub), 2025)
Fashion plays a significant role in shaping self-identity, particularly among Indonesian millennials living in the digital and globalized era. This study aims to analyze the role of fashion as a visual communication medium in expressing millennials' self-identity through Roland Barthes' semiotic approach. Using a qualitative literature review method, data were collected from relevant secondary sources, such as journal articles, books, and dissertations. The analysis reveals that fashion functions as a system of signs containing denotative meanings, such as color or design, and connotative meanings reflecting personality, social status, or local culture. Social media platforms, such as Instagram and TikTok, serve as key arenas for millennials to showcase their fashion styles and construct their public identities. The findings affirm that fashion not only reflects but also shapes self-identity within the context of negotiating globalization and locality. This study contributes theoretically to semiotic studies and practically to the fashion and marketing industries. However, the absence of direct empirical data is a limitation, suggesting that future research should integrate field methods to deepen understanding of the interaction between fashion and millennial identity.